What's New in Pediatric Upper Extremity Sports Injuries?. Issue 2 (February 2018) - Beck, Jennifer J.; Richmond, Connor G.; Tompkins, Marc A.; Heyer, Ann; Shea, Kevin G.; Cruz, Aristides I.
Abstract : Background: Sports injuries are common in pediatric and adolescent patients and the evaluation and treatment of these injuries continues to evolve. The purpose of this review is to provide a comprehensive appraisal of the most recent literature, highlighting updates on sports-related upper extremity injuries in pediatric patients. Methods: An electronic search of the PubMed, EMBASE, and Google Scholar databases was performed for keywords related to pediatric overhead athletes, osteochondritis dissecans (OCD) of the capitellum, medial epicondyle fractures, shoulder instability, and clavicle fractures. Search results were filtered by publication date to yield articles published electronically or in print on or after January 1, 2013 to May 30, 2017. Papers were selected based on expert opinion and consensus by the authors and included if deemed to have contributed important findings to the above topics. Results: A total of 51 articles were deemed to have contributed significant findings to the literature: 11 overhead athlete, 9 OCD of the capitellum, 6 medial epicondyle fractures, 17 shoulder instability, and 8 clavicle fractures. The level of evidence for most studies was either Level III or IV. Conclusions: Overuse and traumatic conditions of the pediatric elbow including UCL tear, capitellar OCD, and medial epicondyle fractures represent a significant portion of injuries in the overhead athlete. Research in the prevention and treatment of primary and recurrent shoulder instability in young athletes continues to evolve. The operative treatment of clavicle fractures in adolescents has been increasing without a commensurate increase in the level of evidence supporting such treatment. Advances have been made in the treatment of sports-related upper extremity injuries in pediatric patients, however, high-level, comparative outcomes research in many areas is lacking and this review may help inform topics for future study. Level of Evidence: Level IV—Literature review.